Вы находитесь на странице: 1из 10

Business Mathematics II

Submitted by (Group Members): Submitted to:


Anshaj Shrestha Mr. Guru Prasad Rijal
Bipin Gurung
Dipesh Raj Pandey
Ganesh Gurung
Karan Rai
Sanjay Gautam
Sauharda Kushal
Sushant Singh Bhandari
ACKNOWLEDGEMENT

We would like to thank our Mathematics teacher, Mr. Guru Prasad Rijal
for his support in preparing this report. His vital guidance and
supervision helped us a lot in the completion of this report which has
been prepared as per the course requirement.
Thank You
Anshaj Shrestha
Bipin Gurung
Dipesh Raj Pandey
Ganesh Gurung
Karan Rai
Sanjay Gautam
Sauharda Kushal
Sushant Singh Bhandari
1. Solve the equations by using Cramer’s rule:

x+y+z=9

2x+5y+7z=52

2x+y-z=0

Solution:

The given system of equations can be written in matrix form as:

1 1 1 𝑥 9
(2 5 7 ) [𝑦] = (52)
2 1 −1 𝑧 0
Now,

1 1 1
|A|= |2 5 7|
2 1 −1
5 7 2 7 2 5
= 1| |-1| |+1| |
1 −1 2 −1 2 1
= 1(-5-7)-1(-2-14) +1(2-10)

= -12+16-8

= -4≠0

So, 𝐴−1 exists.

9 1 1
D1= |52 5 7|
0 1 −1
= 9(-5-7)-52(-1-1) +0

= 9×-12-52×-2

= -108+104

= -4

1 9 1
D2= |2 52 7 |
2 0 −1
= -9(-2-14) +52(-1-2) +0
= -9×-16+52×-3

= 144-156

= -12

1 1 9
D3= |2 5 52|
2 1 0
= 9(2-10)-52(1-2) +0

= 9×-8-52×-1

= -72+52

= -20

By Cramer’s rule, we have,

x= D1/D

= -4/-4

=1

y= D2/2

= -12/-4

=3

z= D3/D

= -20/-4

=5

So, x=1, y=3 and z=5


2. A movie theatre has a seating capacity of 3000 people. The number of people attending a
show at p dollars per ticket is q=18000/p-1500. Currently the price is $6 per ticket.

i) Is the demand elastic or inelastic at p=$6?

ii) If the price is lowered, will revenue increase or decrease?

Solution:

The number of people attending a show at price p dollars per ticket is

q=18000/p-1500

and Price (p)=$6


𝑑𝑞 𝑑𝑝−1 𝑑1500
Here, 𝑑𝑝 = 18000 –
𝑑𝑝 𝑑𝑝

= 18000×-1𝑝−2 – 0

= -18000/𝑝2

When p=6, q= 18000/6-1500

= 1500

We know,
𝑑𝑞
Elasticity of demand (𝑛𝑑 ) = -p/q×𝑑𝑝

−𝑝 −18000
= ×
𝑞 𝑝2

18000
= 𝑝𝑞

18000
= 6×1500

= 2>1

Since 𝑛𝑑 >1, demand is elastic at p=$6.

ii) If the price is lowered, revenue will increase.


3. If C(x) =a𝑥 2 +bx+c be the cost function and x be the commodity produced then prove that
1
slope of AC= 𝑋(MC-AC). Verify this relation if C(x) =100+x+2𝑥 2 .

Solution:

Given, C(x) = a𝑥 2 +bx+c


𝐶
Now, Average cost (AC) = 𝑋

𝑎𝑥 2 +𝑏𝑥+𝑐
= 𝑐

𝑐
= ax+b+ 𝑥

𝑑𝑐
Marginal Cost (MC) = 𝑑𝑥

𝑑𝑥 2 𝑑𝑥 𝑑𝑐
= a 𝑑𝑥 + b𝑑𝑥 + 𝑑𝑥

= 2ax+b

Now,
𝑐
MC-AC = 2ax+b-ax-b- 𝑥

𝑐
= ax- 𝑥

1 𝑐
1/x (MC-AC) = 𝑋(ax-𝑥)

𝑐
= a - 𝑥2

Also,
𝑐
𝑑𝐴𝐶 𝑑(𝑎𝑥+𝑏+ )
𝑥
=
𝑑𝑥 𝑑𝑥

𝑑𝑥 𝑑𝑏 𝑑𝑥 −1
= a𝑑𝑥 + 𝑑𝑥 + c 𝑑𝑥

= a+0+c × -1𝑥 −2
𝑐
= a- 𝑥 2

𝑑𝐴𝐶 1 𝑐
So, = 𝑋 (MC-AC) = a- 𝑥 2
𝑑𝑥
1
Hence, Slope of AC= 𝑋 (MC-AC)

For C(x) = 100+x+2𝑥 2

Comparing with C(x) = a𝑥 2 + bx + c, we get,

a=2, b=1 and c=100

Now,
1 𝑐
(MC-AC)= a- 𝑥 2
𝑥

100
=2- 𝑥2

𝑑𝐴𝐶 𝑐
Also, = a- 𝑥 2
𝑑𝑥

100
=2- 𝑥2

1 100
So, Slope of AC= 𝑥 (MC-AC) = 2 - 𝑥2
𝜕𝑢 𝜕𝑢 𝜕𝑢
4. If u= log (𝑥 2 +𝑦 2 +𝑧 2 ), prove that x𝜕𝑥 + y𝜕𝑦 + z 𝜕𝑧 = 2.

Solution:

Here, u= log (𝑥 2 + 𝑦 2 + 𝑧 2 )

Now,
𝜕𝑢 𝜕log (𝑥 2 +𝑦2 +𝑧 2 )
=
𝜕𝑥 𝜕𝑥

𝜕log (𝑥 2 +𝑦2 +𝑧 2 ) 𝜕(𝑥 2 +𝑦 2 +𝑧 2 )


= ×
𝜕𝑥 𝜕𝑥

1
= (𝑥 2 +𝑦 2+𝑧 2 ) × 2x

2𝑥
= (𝑥 2 +𝑦 2+𝑧 2 )

Similarly,
𝜕𝑢 2𝑦 𝜕𝑢 2𝑧
= (𝑥 2 +𝑦 2+𝑧 2 ) and = (𝑥 2 +𝑦 2 +𝑧 2)
𝜕𝑦 𝜕𝑧

Now,
𝜕𝑢 𝜕𝑢 𝜕𝑢
L.H.S = x𝜕𝑥 + y𝜕𝑦 + z 𝜕𝑧

2𝑥 2 2𝑦 2 2𝑧 2
= (𝑥 2 +𝑦 2+𝑧 2 ) + (𝑥 2 +𝑦 2 +𝑧 2 ) + (𝑥 2 +𝑦 2 +𝑧 2 )

2𝑥 2 +2𝑦 2 +2𝑧 2
= (𝑥 2 +𝑦 2 +𝑧 2 )

=2

= R.H.S Proved

So, L.H.S = R.H.S Proved


5. Find the first order and the second order total differentials of v = 𝑒 𝑥+3𝑦 .

Solution:

Here, v = 𝑒 𝑥+3𝑦
∂V
Now, 𝑓𝑥 = ∂x

∂ex+3y ∂(x+3y)
= ∂(x+3y) × ∂x

= ex+3y × 1

= 𝑒 𝑥+3𝑦
∂V
𝑓𝑦 = ∂y

∂ex+3y ∂(x+3y)
= ∂(x+3y) × ∂y

= 𝑒 𝑥+3𝑦 × 3

= 3 𝑒 𝑥+3𝑦

We know,

First order differential is

dv = 𝑓𝑥 dx + 𝑓𝑦 dy

= (𝑒 𝑥+3𝑦 )dx + ( 3𝑒 𝑥+3𝑦 )dy

= 𝑒 𝑥+3𝑦 (dx+3dy)

Again,
𝜕(𝑓𝑥 )
𝑓𝑥𝑥 = 𝜕𝑥

∂ex+3y ∂(x+3y)
= ×
∂(x+3y) ∂x

= ex+3y × 1

= 𝑒 𝑥+3𝑦
𝜕(𝑓𝑦 )
𝑓𝑥𝑦 = 𝜕𝑥

∂ex+3y ∂(x+3y)
= ∂(x+3y) × ∂y

= 𝑒 𝑥+3𝑦 × 3

= 3 𝑒 𝑥+3𝑦
𝜕(𝑓𝑦 )
𝑓𝑦𝑦 = 𝜕𝑦

∂ex+3y ∂(x+3y)
=3 ×
∂(x+3y) ∂y

= 3 × 𝑒 𝑥+3𝑦 × 3

= 9 𝑒 𝑥+3𝑦

We know,

Second order differential is

𝑑 2 V = 𝑓𝑥𝑥 𝑑𝑥 2 + 2 𝑓𝑥𝑦 dxdy + 𝑓𝑦𝑦 d𝑦 2

= (𝑒 𝑥+3𝑦 )d𝑥 2 + 2×3(𝑒 𝑥+3𝑦 )dxdy + 9(𝑒 𝑥+3𝑦 )d𝑦 2

= (𝑒 𝑥+3𝑦 )(d𝑥 2 +6dxdy+9d𝑦 2 )